2003
DOI: 10.1179/026708303225001902
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of effect of alloying elements on martensite start temperature of steels

Abstract: Making the transformation from austenite to martensite difficult is called stabilisation of austenite, a phenomenon that occurs in many cases. The straightforward method to analyse the influence of a specific factor on the stabilisation of austenite is through its influence on the martensite start (M s ) temperature. This work outlines the use of an artificial neural network to model the M s temperature of engineering steels from their chemical composition and austenite grain size. The results are focussed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 18 publications
2
55
0
Order By: Relevance
“…However, in the left-hand side, upper bainite sheaves can be found. It can be then concluded that the transition from upper to lower bainite occurs at a temperature about 450 C. Table 2 lists the M s temperature of the studied steel calculated from different empirical formulas, 14,[18][19][20][21][22][23] thermodynamic theory, 24) and neural network analysis, [25][26][27] in comparison with the M s experimental value. The free energy change for the transformation of austenite to ferrite of the same composition, ÁG , input in Ghosh and Olson model 24) was calculated using MTDATA.…”
Section: Determination Of M S B S and Lb S Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the left-hand side, upper bainite sheaves can be found. It can be then concluded that the transition from upper to lower bainite occurs at a temperature about 450 C. Table 2 lists the M s temperature of the studied steel calculated from different empirical formulas, 14,[18][19][20][21][22][23] thermodynamic theory, 24) and neural network analysis, [25][26][27] in comparison with the M s experimental value. The free energy change for the transformation of austenite to ferrite of the same composition, ÁG , input in Ghosh and Olson model 24) was calculated using MTDATA.…”
Section: Determination Of M S B S and Lb S Temperaturesmentioning
confidence: 99%
“…The inputs of Ghosh and Olson's model are the chemical composition and the free energy change for the transformation of austenite to ferrite of the same composition, ÁG . More recently, Capdevila et al [25][26][27] developed a model using artificial neural networks for the determination of M s , including the effect of chemical composition and the prior austenite grain size (PAGS) in calculations.…”
Section: Introductionmentioning
confidence: 99%
“…8(a) confirm the high extent of carbon enrichment in austenite after bainite formation since the applicable chemistry range of the neural network model (1.62wt% C) seems to be exceed. 19) Since tensile tests were performed at room temperature, in principle, M S temperatures below 20°C are desired in order to increase the thermal stability of the retained austenite in the microstructure. Likewise, it is important to highlight what a high or low value of M d temperature implies in terms of mechanical stability and the efficiency enhancing ductility.…”
Section: )mentioning
confidence: 99%
“…Both temperatures, M S and M d , give an indication of the thermal and mechanical stability, respectively, of the retained austenite and depend on the retained austenite chemical composition calculated making use of X-ray analysis. M S was calculated by means of a neural network model 19) and M d temperature was calculated using the following equation, 14) ln…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation